2009
DOI: 10.14776/kjpid.2009.16.1.92
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Fatal Myocarditis Associated with Mycoplasma pneumoniae Pneumonia

Abstract: Mycoplasma pneumoniae is a common cause of respiratory tract infections. M. pneumoniae infection frequently manifests with extrapulmonary symptoms such as central nervous system complications, skin or mucosal involvement, and gastrointestinal problems. However, cardiac complications associated with M. pneumoniae are rarely reported. We report the case of a 47-month-old girl who died of fulminant myocarditis associated with M. pneumoniae pneumonia. (Korean J Pediatr Infect Dis 2009;16:92-96)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…In 1979, Pönkä6) reported that among 560 patients with serologically confirmed M. pneumoniae infection, 25 (4.5%) had carditis (19 perimyocarditis and 6 pericarditis). In contrast, in Korea, only 4 cases of M. pneumoniae -associated pericarditis have been reported in pediatric patients 7-10). Clarithromycin and azithromycin are among the drugs of choice for the treatment of respiratory tract infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1979, Pönkä6) reported that among 560 patients with serologically confirmed M. pneumoniae infection, 25 (4.5%) had carditis (19 perimyocarditis and 6 pericarditis). In contrast, in Korea, only 4 cases of M. pneumoniae -associated pericarditis have been reported in pediatric patients 7-10). Clarithromycin and azithromycin are among the drugs of choice for the treatment of respiratory tract infections.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in Korea, only 4 cases of M. pneumoniae -associated pericarditis have been reported in pediatric patients. 7 - 10) Clarithromycin and azithromycin are among the drugs of choice for the treatment of respiratory tract infections. It is important to investigate the association between antibiotic use and resistance as the resistance of common respiratory pathogens to macrolides has been increasing.…”
Section: Introductionmentioning
confidence: 99%
“…그러나 심근표지 자의 상승은 검사 당시 병의 지속시간과 연관이 있고, 상 승이 나타나지 않은 경우도 있으므로, 정상소견을 보인다 고 해서 심근염을 배제할 수는 없다. 미코플라스마와 심근염의 연관성에 대해 국내에서 사례 보고가 있었다 19) . 미코플라스마의 경우 주로 소아에서 호 흡기 증상으로 발현되어 편도염이나 기관지염, 비전형 폐 렴과 같은 호흡기 질환을 일으키는 것으로 알려져 있으나, 드물게 급성 심근염이나 심막염을 일으키기도 하며, 혈액 검사에서 감염이 확인된 환자에서 1.0-8.5%까지 나타나 는 것으로 보고되고 있다 [20][21][22] .…”
unclassified